Satisfaction level of students towards telecommunication service in Bangladesh - Kumar, Dhanonjoy; Haque, A. K. M. Ahasanul (2019)
Customer satisfaction is a term frequently used in marketing. It is a measure of how products and services supplied 6y a company meet or improve on customer expectation. This study seeks to explore cus tomer saus faction and its influencing factors of the mobile phone operation industry in Bangladesh. Both primary and secondary data have been collected for the purpose of the study. Primary data were collected through a quesñorinaire and the observation method. Secondary data were collected directly by the researcher from different secondary sources. This study is conducted on 320 Grameenphone (GP) users in Bangladcsh. In the course of data analysis, frequency percentage, bar charts, test of reliability, KMO -Bartlett test, exploratory factor analysis, correlation and linear regression analysis have been used. The result shows that a significant re1ati’onship exists bebeen customer satisfaction and service quality, network, call rate, internet facility and social responsibility. The result also shows that service quality, network, internet facility and social responsibility are significant predictors of customer satisfaction. Overall the Satisfacuon level of sindents of Grameenphone limited is not up to the mark.